Readiness of Poultry Slaughterhouse Business Actors in Socah District, Bangkalan Regency towards Halal Certification - Agustina, Yulia; Nasrullah, M. Faiz (AL-QARDH, 2024)
This study aims to analyze the readiness of poultry slaughterhouse operators in Socah Subdistrict, Bangkalan Regency towards halal certification. Halal certification is increasingly important as the demand for halal products rises globally. Based on PMA No. 26/2019, halal certification must be implemented gradually, starting with food and beverage products. However, in Bangkalan, it is still difficult to ensure that poultry products sold meet halal standards. This study used a qualitative method with a combination of literature study and field observation. The results show that business actors are not ready to implement halal certification, mainly due to a lack of information and understanding of the certification process. Despite having a Business Identification Number (NIB), they have not proceeded to the halal certification process. Limited access to information, financing, and lack of support from the government are the main obstacles. Business actors show readiness to participate in socialization and training related to halal certification to understand the steps required. This study suggests increasing socialization and training to encourage business actors to obtain halal certification and increase awareness and compliance with applicable regulations. Keywords: Business Readiness, Poultry Slaughterhouse, Halal Certificationand compliance with applicable regulations.